Kesantunan dalam Ritual Pernikahan Masyarakat Hindu-Bali; Kajian Etnopsikolingustik Religius - Wardani, Kadek Devi Kalfika Anggria (Universitas Pendidikan Ganesha, 2020)
The study which is descriptive qualitative in nature, aims to investigate preference of politeness strategies by Balinese Hindu-community in traditional marriage ritual. Data was collected using interview and observation methods. Based on the results of data analysis, this research shows that the form of politeness that arises can be seen in terms of place, time, to the leaders of the people, during preparation, implementation, disclosure of the relationship with the Almighty, and after the completion of the ritual. The different forms of politeness that emerge can be seen from the use of Balinese in various levels which are adjusted to the social distance and speech situation. Besides being seen from the use of language, linguistic politeness is also evident from the attitude, intonation, and tone of the speaker. The difference in the form of politeness is intentionally raised to cause certain psychological impacts on the interlocutor.